Let-7b-5p sensitizes breast cancer cells to doxorubicin through Aurora Kinase B - Murat Kaya; Asmaa Abuaisha; Ilknur Suer; Selman Emiroglu; Semen Önder; Evren Onay Ucar; Mustafa Nuri Yenerel; Sukru Palanduz; Kivanc Cefle; Sukru Ozturk; Zeyneb Kurt (PLoS ONE, 2025)
MicroRNAs (miRNAs) are small, non-coding RNAs that regulate the expression level of the target genes in the cell. Breast cancer is responsible for the majority of cancer-related deaths among women globally. It has been proven that deregulated miRNAs may play an essential role in the progression of breast cancer. It has been shown in many cancers, including breast cancer, that aberrant expression of miRNAs may be associated with drug resistance. This study investigated the effect of let-7b-5p, detected by bioinformatics methods, on Dox resistance through the Aurora Kinase B (AURKB) gene. In silico analysis using publicly available miRNA expression, GEO datasets revealed that let-7b-5p significantly downregulated in BC. Further in silico studies revealed that of the genes among the potential targets of let-7b-5p, AURKB was the most negatively correlated and may be closely associated with Dox resistance. Expression analysis via quantitative PCR confirmed that let-7b-5p was downregulated and AURKB was upregulated in breast cancer tissue samples. Later, functional studies conducted with MCF-10A, MCF-7, and MDA-MB-231 cell lines demonstrated that let-7b-5p inhibits cancer cells through AURKB and sensitizes them to Dox resistance. In conclusion, it has been shown that the let-7b-5p/AURKB axis may be significant in breast cancer progression and the disruption in this axis may contribute to the trigger of Dox resistance.